Relationship between contrast-enhanced ultrasound combined with ultrasound resolution microscopy imaging and histological features of hepatocellular carcinoma. - Wang, Feiqian; Yu, Jingtong; Lu, Xingqi; Numata, Kazushi; Ruan, Litao; Zhang, Dong; Liu, Xi; Li, Xiaojing; Wan, Mingxi; Zhang, Wenbin; Zhang, Guanjun (Abdominal Radiology, 2025)
Objectives: Using contrast-enhanced ultrasound (CEUS) and ultrasound resolution microscopy (URM) imaging, this study aimed to evaluate the relationship between microvascular parameters of small hepatocellular carcinoma (sHCC) (≤ 3 cm) and microscopic histological features, which include vessels encapsulating tumour clusters (VETC), microvascular invasion (MVI), and histological grade. Methods: Sixteen patients with solitary resected sHCC were prospectively enrolled. CEUS and URM were performed one week before resection. All "ratio" refers to comparisons between the active area (where CEUS microbubble show visible motion track by URM) and the entire lesion. Blood vessel complexity (ratio), blood vessel density (ratio), area (ratio), flow velocity, blood vessel diameter, and perfusion index ("flow velocity" × "vessel ratio") were analysed using URM. The relationships between URM parameters and microscopic histological features (MVI, VETC, and histological grade) were analysed. Results: There were 5 (31.3%), 8 (50%), and 7 (43.7%) cases of poorly differentiated, MVI-positive, and VETC-positive HCC, respectively. The mean velocity of the entire lesion was higher in the poorly differentiated group than that in the moderately differentiated group (p = 0.026). The complexity ratio (MVI-positive: 1.07 ± 0.03, MVI-negative: 1.03 ± 0.02, p = 0.012), area ratio (MVI-positive: 0.63 ± 0.18, MVI-negative: 0.39 ± 0.16, p = 0.017), and perfusion index (MVI-positive: 8.67 ± 1.88, MVI-negative: 6.42 ± 0.94, p = 0.009) were greater in MVI-positive HCCs. The density ratio (VETC-positive: 1.30 ± 0.19, VETC-negative: 1.10 ± 0.05, p = 0.006) was larger in VETC-positive HCCs. Conclusion: Higher blood flow velocity and area of HCC lesions, and higher blood vessel complexity and density may be related to microscopic histological features. This relationship might provide a strategy of using URM for preoperative non-invasive diagnostic VETC, MVI, and histological grade in the future.